If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -9 = 11 + 6x Reorder the terms: -9 + 5x = 11 + 6x Solving -9 + 5x = 11 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -9 + 5x + -6x = 11 + 6x + -6x Combine like terms: 5x + -6x = -1x -9 + -1x = 11 + 6x + -6x Combine like terms: 6x + -6x = 0 -9 + -1x = 11 + 0 -9 + -1x = 11 Add '9' to each side of the equation. -9 + 9 + -1x = 11 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 11 + 9 -1x = 11 + 9 Combine like terms: 11 + 9 = 20 -1x = 20 Divide each side by '-1'. x = -20 Simplifying x = -20
| 5y=10/9 | | sin(2x+30)=0.8 | | 5n+5=80 | | 7p-3p+4=-4p+2+10 | | 6x+5y=-100+10 | | 2h+10= | | 9(3a+1)+2(a-3)= | | 8y-4=-2y+2 | | -2(2)-4(-2)(3)+(3)(2)= | | 8n+4=100 | | 2x-(9-3x)=7+4(2x+1) | | 2k-8(6k+5)=7k-40 | | 16+22+48= | | 3-3*6+2=2 | | 4(2x+2)-3x=15(x-2)-72 | | 8x+8-3=15x-30-72 | | 5+5x+2x=54 | | 0.4(8+t)=5th+0.9 | | 3(4x-5)+2(11-2x)=39 | | 2b-5=11 | | 2(2x+8)=3(2x+14) | | y+7*0=11 | | 8k-7k-16*3k=-21 | | 2x-8=8x+6 | | 4/10=x/12 | | 7x+3=3x+75 | | x^2-4y^2-16y-20=0 | | 0=(8sinx)/x | | 5y+5(2+3)=4y+1 | | 5x+10=4(x-2) | | t^2+6t-20=0 | | 3[4(4+1)]= |